2009
DOI: 10.1111/j.1478-3231.2009.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal liver necrosis appears early after partial hepatectomy and is dependent on T cells and antigen delivery from the gut

Abstract: A distinct pattern of early focal hepatic necrosis is observed following extensive PH in mice. T cells infiltrating the liver immediately after PH and gut-derived antigens are indispensable for the observed liver necrosis and may thus provide therapeutic targets to ameliorate liver damage following PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…After mice were euthanized, the livers were removed and small pieces from different lobes of the livers were fixed in 10% neutral buffered formalin, embedded in paraffin, sectioned at 5 μM, and stained with hematoxylin and eosin (H&E) for necrosis and other structural changes. The degree of tissue necrosis was evaluated and scored as previously reported (Rudich et al, 2009). The necrotic score indicated the number of necrotic foci per low-power magnification field (×100) in at least 10 fields per slide.…”
Section: Methodsmentioning
confidence: 99%
“…After mice were euthanized, the livers were removed and small pieces from different lobes of the livers were fixed in 10% neutral buffered formalin, embedded in paraffin, sectioned at 5 μM, and stained with hematoxylin and eosin (H&E) for necrosis and other structural changes. The degree of tissue necrosis was evaluated and scored as previously reported (Rudich et al, 2009). The necrotic score indicated the number of necrotic foci per low-power magnification field (×100) in at least 10 fields per slide.…”
Section: Methodsmentioning
confidence: 99%
“…LPS as a toll-like receptor 4 ligand has been reported to play a central role in the initiation of liver regeneration [23, 24]. Rudich et al even found reduced hepatocyte proliferation in partial hepatectomized mice after removing LPS from the gut via antibiotic pretreatment [25]. In addition, hepatocyte-specific deletion of NEMO, the regulatory subunit of the NF-κB complex, leads to impaired liver regeneration after partial hepatectomy independent of an inflammation [26].…”
Section: Discussionmentioning
confidence: 99%
“…A moderate inflammatory stimulus seems to be essential for the initiation of liver regeneration, whereas marked inflammatory reactions have a negative impact [27, 28]. Thus, complete elimination of LPS via antibiotic bowel decontamination [25] prevents the stimulatory effect. Tail vein injection of LPS in rats [29] or intraperitoneally application in mice induces the accumulation of neutrophils in the liver [30].…”
Section: Discussionmentioning
confidence: 99%
“…Focal and/or patchy necrosis is an important finding after hepatectomy 24–27 . Progressive necrosis was confirmed from the early postoperative period, 24,25,27 and we collected all samples at 6 h after 90% hepatectomy. There were eight mice in each group.…”
Section: Methodsmentioning
confidence: 99%